Analisis Resepsi Objektifikasi Seksual Dalam Tayangan Puteri Indonesia 2020 - Kilau Riksaning Ayu; Sunarto Sunarto (Jurnal Audience: Jurnal Ilmu Komunikasi, 2021)
Abstract Rejection and support are present in the implementation of the Puteri Indonesia beauty contest. There were rejections from feminists and religious organizations regarding the issue of sexual objectification. On the other hand, support is present through the enthusiasm of the community, one of which is through the acquisition of high ratings in the Puteri Indonesia 2020 show. The reality of the support and popularity of beauty contests behind sexual objectification has become a research problem. Based on the situation, this study aims to determine the audiences' reception towards the sexual objectification of contestants in the Puteri Indonesia 2020 program. This study involved eight informants who had watched the Puteri Indonesia 2020 show. Based on the research results, the audience's meaning system functioned theoretically to develop concepts from Standpoint Theory and Reception Theory. The study results apply the concept of Standpoint Theory, such as a standpoint of the dominant group, the interests of the dominant group, and situated knowledge that is useful for explaining the phenomenon of sexual objectification in the Puteri Indonesia 2020 show. The concept of the Reception Theory shows the audience's active role through a meaning system of 8 informants based on 10 preferred readings, which resulted in 3 positions of meaning, such as dominant, negotiation, and opposition. The majority of the meanings of the eight informants are in a dominant position. 4 Female informants showed 18 dominant meanings, 12 negotiations, and 10 oppositions. Meanwhile, 4 male informants showed 22 dominant meanings, 17 negotiations, and 1 opposition. The research results add to reception studies for established program genres. In this case, the Puteri Indonesia contest has proven existence until 2020 that successfully held and broadcast on national television stations 25 times.Keywords: beauty pageant; preferred reading; Puteri Indonesia; reception analysis; sexual objectification  Abstrak Penolakan dan dukungan hadir dalam penyelenggaraan kontes kecantikan Puteri Indonesia. Penolakan hadir dari para feminis dan organisasi agama terkait isu objektifikasi seksual. Di sisi lain, dukungan hadir melalui antusiasme masyarakat, salah satunya terlihat melalui perolehan rating tinggi dalam penayangan acara Puteri Indonesia 2020. Realita berupa dukungan dan kepopuleran kontes kecantikan di balik isu objektifikasi seksual menjadi permasalahan penelitian. Untuk itu, studi resepsi digunakan untuk mengetahui pandangan khalayak terkait objektifikasi seksual dalam kontes Puteri Indonesia 2020. Penelitian ini melibatkan 8 informan yang telah menyaksikan acara Puteri Indonesia 2020. Sistem pemaknaan khalayak berdasarkan hasil penelitian berfungsi secara teoritis mengembangkan konsep dari Teori Standpoint dan Teori Resepsi. Hasil penelitian menerapkan konsep Teori Standpoint yaitu, sudut pandang kelompok berkuasa, kepentingan kelompok berkuasa, dan pengetahuan tersituasi yang berguna untuk menjelaskan fenomena objektifikasi seksual dalam tayangan Puteri Indonesia 2020. Konsep dari Teori Resepsi menunjukkan peran aktif khalayak melalui sistem pemaknaan 8 informan berdasarkan 10 preferred reading yang menghasilkan 3 posisi pemaknaan yaitu: dominan, negosiasi, dan oposisi. Mayoritas pemaknaan 8 informan berada dalam posisi dominan. 4 Informan perempuan menunjukkan 18 makna dominan, 12 negosiasi, dan 10 oposisi. Sedangkan, 4 Informan laki-laki menunjukkan 22 makna dominan, 17 negosiasi, dan 1 oposisi.  Hasil penelitian menambah studi resepsi pada genre program mapan. Dalam hal ini, kontes Puteri Indonesia membuktikan eksistensinya hingga tahun 2020 telah berhasil diselenggarakan dan ditayangkan di stasiun televisi nasional sebanyak 25 kali.   Kata Kunci: analisis resepsi; kontes kecantikan; objektifikasi seksual; preferred reading; Puteri Indonesia